If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4i + -5)(6 + -7i) = 0 Reorder the terms: (-5 + 4i)(6 + -7i) = 0 Multiply (-5 + 4i) * (6 + -7i) (-5(6 + -7i) + 4i * (6 + -7i)) = 0 ((6 * -5 + -7i * -5) + 4i * (6 + -7i)) = 0 ((-30 + 35i) + 4i * (6 + -7i)) = 0 (-30 + 35i + (6 * 4i + -7i * 4i)) = 0 (-30 + 35i + (24i + -28i2)) = 0 Combine like terms: 35i + 24i = 59i (-30 + 59i + -28i2) = 0 Solving -30 + 59i + -28i2 = 0 Solving for variable 'i'. Factor a trinomial. (-5 + 4i)(6 + -7i) = 0Subproblem 1
Set the factor '(-5 + 4i)' equal to zero and attempt to solve: Simplifying -5 + 4i = 0 Solving -5 + 4i = 0 Move all terms containing i to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + 4i = 0 + 5 Combine like terms: -5 + 5 = 0 0 + 4i = 0 + 5 4i = 0 + 5 Combine like terms: 0 + 5 = 5 4i = 5 Divide each side by '4'. i = 1.25 Simplifying i = 1.25Subproblem 2
Set the factor '(6 + -7i)' equal to zero and attempt to solve: Simplifying 6 + -7i = 0 Solving 6 + -7i = 0 Move all terms containing i to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -7i = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -7i = 0 + -6 -7i = 0 + -6 Combine like terms: 0 + -6 = -6 -7i = -6 Divide each side by '-7'. i = 0.8571428571 Simplifying i = 0.8571428571Solution
i = {1.25, 0.8571428571}
| -4/3a=8 | | 4x*2x+10= | | -24-n=32 | | (5x^2-3y)(x^2-y)=0 | | x+(x+22)+x+(x+22)=720 | | 6x+1=3x+-11 | | 3x-2=25+6x | | -4=m/20-5 | | 81-42=w | | -5(t-1)+8t=5t-4 | | 137-w=274 | | 9j-9=9+3j+9j | | 81-42= | | 3(2x-3)=8x-5 | | 27z-66=z-(-60) | | 6(x-1)+5=3x+3(-1+x) | | 27z-60=z-(-60) | | t/5=16 | | 4x-y+11=0 | | 7x+7-9x=13-15x+13x-6 | | 7-p+5p=9 | | W(3w+2)=456 | | 1.5x+3.5x-2=18 | | 30x+25y=280 | | -11z-50=z-(-8) | | 3=d | | 70+60= | | 4y=y+-20 | | (7y/8)-(3y/5)=11/2 | | 2y+10x+18=4 | | 8x^2-y^2=8 | | 13.95+9.95= |